Single Ether‐Based Side Chains in Conjugated Polymers: Toward Power Factors of 2.9 mW m−1 K−2. Issue 2 (30th November 2021) - Durand, Pablo; Zeng, Huiyan; Biskup, Till; Vijayakumar, Vishnu; Untilova, Viktoriia; Kiefer, Céline; Heinrich, Benoît; Herrmann, Laurent; Brinkmann, Martin; Leclerc, Nicolas
Abstract: Combining side chain engineering and controlled alignment of PBTTT is an effective strategy to produce oriented thin films with improved thermoelectric performance when doped sequentially with the acceptor molecule hexafluoro‐tetracyanonaphthoquinodimethane (F6 TCNNQ). The substitution of linear alkyl side‐chains ( n ‐C12 ) with a chain of identical length including an ether function ( n ‐C7 OC4 ) leads to a new class of slightly polar PBTTT polymers, preserving the ease of synthesis and air stability of alkylated PBTTTs. This side‐chain modification improves the structural order of PBTTT backbones and the thermo‐mechanical properties of the polymer. It then can be oriented by high temperature rubbing up to 240 ° C to reach very high dichroic ratios up to 20 thanks to enhanced cohesive forces within side‐chain layers. The side chain polarity of n ‐C7 OC4 helps to tune the polymer‐dopant interactions. A multi‐technique approach demonstrates that F6 TCNNQ dopants are randomly oriented in the disordered side chain layers of n ‐C7 OC4 with some evidence of dopant clustering. The combination of improved alignment and random orientation of intercalated F6 TCNNQ dopants helps reach a very high charge conductivity σ = 5 ⋅ 10 4 S cm −1 and a record power factor of 2.9 mW m −1 K −2 in the polymer chain direction. Abstract : The use of an ether‐based side chain leads to a new class of slightly polar PBTTT polymers. This side‐chain preserves ease of synthesis and air stability while improving the polymer structural order and thermomechanical properties. After rubbing and hexafluoro‐tetracyanonaphthoquinodimethane‐doping, very high charge conductivity σ = 5 ⋅ 10 4 S cm −1 and a record power factor of 2.9 mW m −1 K −2 are obtained.